Association between personality characteristics and sleep quality among Chinese middle-aged and older adults: evidence from China family panel studies - Zhen Wang; Zhi Zeng (BMC, 2023)
Abstract Background Poor sleep quality will have adverse effects on physical and mental health, quality of life and other aspects of middle-aged and older adults. Sleep quality is affected by many factors. Whether the sleep quality measures of the participants had changed in the previous or subsequent time period is not easily taken into account. Moreover, there have been no studies on this topic in Chinese middle-aged and older adults. The objective of this study was to mitigate the bias of sleep quality assessment, and analyze the association between personality traits and sleep quality in Chinese middle-aged and older adults. Methods The data came from the China Family Panel Studies (CFPS). A total of 6031 participants aged ≥ 45 years were included in this study. Personality characteristics were evaluated based on the scores of each dimension of Big Five personality traits. Sleep duration and sleep perception were used as indicators to measure sleep quality. Logistic models were used to analyze the relationship between personality traits and sleep duration or sleep perception, respectively. Results 4.5% of the participants had abnormal sleep duration, and 14.4% had a pessimistic sleep perception. Conscientiousness was rated the highest among the personality traits (3.97 ± 0.6). Participants with higher scores for extraversion personality traits had more normal sleep duration (OR = 0.77, 95% CI: 0.64-0.93) and more optimistic sleep perception (OR = 0.86, 95% CI: 0.76-0.96). Using the Internet and feeling unwell in the past week have a moderating effect on the impact of conscientiousness personality characteristics on sleep duration or sleep perception, respectively (but not overall sleep quality). In addition, participants with a spouse or no recent physical discomfort tended to have a normal sleep duration and a more optimistic sleep perception. Conclusions The higher the score of extraversion personality traits, the better the overall sleep quality of middle-aged and older adults. Having a spouse and feeling unwell were the important factors affecting their sleep quality. Specific personality traits intervention should be carried out for middle-aged and older adults with poor sleep quality to make their personality traits are closer to extraversion. In addition, middle-aged and older adults without spouses should be encouraged to marry or remarry. We will strengthen health management and medical expenditures for middle-aged and older adults.